Potential effect of fiddler crabs on organic matter distribution: A combined laboratory and field experimental approach - Natálio, Luís F. [UNESP]; Pardo, Juan C.F. [UNESP]; Machado, Glauco B.O.; Fortuna, Monique D. [UNESP]; Gallo, Deborah G. [UNESP]; Costa, Tânia M. [UNESP] (Elsevier, 2017)
Bioturbators play a key role in estuarine environments by modifying the availability of soil elements, which in turn may affect other organisms. Despite the importance of bioturbators, few studies have combined both field and laboratory experiments to explore the effects of bioturbators on estuarine soils. Herein, we assessed the bioturbation potential of fiddler crabs Leptuca leptodactyla and Leptuca uruguayensis in laboratory and field experiments, respectively. We evaluated whether the presence of fiddler crabs resulted in vertical transport of sediment, thereby altering organic matter (OM) distribution. Under laboratory conditions, the burrowing activity by L. leptodactyla increased the OM content in sediment surface. In the long-term field experiment with areas of inclusion and exclusion of L. uruguayensis, we did not observe influence of this fiddler crab in the vertical distribution of OM. Based on our results, we suggest that small fiddler crabs, such as the species used in these experiments, are potentially capable of alter their environment by transporting sediment and OM but such effects may be masked by environmental drivers and spatial heterogeneity under natural conditions. This phenomenon may be related to the small size of these species, which affects how much sediment is transported, along with the way OM interacts with biogeochemical and physical processes. Therefore, the net effect of these burrowing organisms is likely to be the result of a complex interaction with other environmental factors. In this sense, we highlight the importance of performing simultaneous field and laboratory experiments in order to better understanding the role of burrowing animals as bioturbators.
Keywords: Bioturbation; Burrows; Estuaries; Genus Leptuca; Sediment transport